Relationship of new markers of kidney damage and vascular status in patients with arterial hypertension (Eurasian Medical Research Periodical, 2022)
Arterial hypertension (AH) and chronic kidney disease (CKD) are closely associated with damage to the vascular wall, which is expressed in deterioration of endothelial function and increased vascular stiffness. Accordingto numerous studies, endothelial dysfunction(ED) is a key component of atherogenesis, is associated with the presence of elevated systolic blood pressure (SBP), and underlies therenocardiovascular interaction, being the basis of pathogenesis.